Detail land use script in web application for Sultane land of Pekan, Pahang, Malaysia - Hj. Mohd. Noor, Norzailawati; Abdullah, Alias; Zakariya, Khalilah; Ibrahim, Illyani; Nizarudin, Norhanis Diyana; N Murtaza, Fatin Farhana (2021)
Protection on the actual script for land use survey on IIUM Land use and Landscape Character Survey Tool (i-LULACAT) developed for data collection in Kajian Meningkatkan Imej Serta Identiti Bandar Diraja Pekan, Pahang. The question scripts are designed for 6 villages in Pekan Sultane Land that contains approximately more than 1300 households.